Employment effects of US minimum wage policy - Liu, Shanshan; Hyclak, Thomas (Journal of Public Governance, 2015)
A strong argument against raising the minimum wage, often voiced in US policy debates, is that a higher minimum wage will have adverse effects on job opportunities. Considerable effort has been devoted to providing quantitative estimates of the employment effects of the minimum wage with quite mixed results. We review this literature before turning to estimates of the impact of state level differences in the level of the minimum wage on youth employment in local labor markets in the Great Lakes Region of the US. We find that a higher minimum wage level is associated with higher earnings, lower employment, and reduced worker turnover for those in the 14 to 18 age group. For workers aged 19 to 21 and 22 to 24, we find less consistent evidence of important minimum wage effects on earnings and employment.